Pengaruh Profitabilitas dan Kesempatan Investasi Terhadap Kebijakan Dividen Tunai Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Fattah, Ilham A (Economics and Digital Business Review, 2024)
This study was conducted to analyze the influence of profitability and investment opportunities on cash dividend policy in companies listed on the Indonesia Stock Exchange from 2009 to 2012. The population in this study consisted of 552 companies listed on the Indonesia Stock Exchange. Using purposive sampling method as the sampling technique, the sample in this study consisted of 152 companies listed on the Indonesia Stock Exchange from 2009 to 2012. The data will be analyzed using multiple linear regression analysis. The results of the study indicate that return on investment (ROI) and market value to book value of asset (MVBVA) simultaneously influence dividend payout ratio (DPR) by 14.5% with a significant value of 0.000. Meanwhile, it was found that return on investment (ROI) positively influences dividend payout ratio (DPR) with a significant value of 0.000, and market value to book value of asset (MVBVA) negatively influences dividend payout ratio (DPR) with a significant value of 0.007.